Determining the Key Capacities of Effective Leaders in Malaysian Public and Private Focused Universities - Ghasemy, Majid; Hussin, Sufean; Razak, Ahmad Zabidi Abdul; Maah, Mohd Jamil; Ghavifekr, Simin (SAGE Publications, 2018)
The study was undertaken to identify the essential leadership capabilities and managerial competencies as the key leadership performance drivers in Malaysian focused universities. To collect data, the previously developed scales of capabilities, competencies, and leadership performance in the context of Malaysian Higher Education (HE) were distributed among the leaders in seven public focused and 12 private focused universities. In total, 172 completed surveys were collected among which 94 had been filled out by the leaders in Malaysian public focused and 78 had been completed by leaders in private focused universities. The data were screened and SmartPLS 3 was employed to analyze the data. Also, Finite Mixture Partial Least Squares (FIMIX-PLS) segmentation and Importance–Performance Map Analysis (IPMA) were run to extend the results. The outcome of FIMIX-PLS didn’t reveal unobserved heterogeneity within the data and, through IPMA, change-oriented capability was identified as the main improvement area to be addressed by management activities. Moreover, the implications of the findings were discussed and future directions were recommended.